Security and Privacy Challenges for theIOT-based Smart Homes with Limited Resources and Adoption Immaturity - Gondal, Farzana Kausar (Innovative Computing Review, 2021)
The Internet of Things (IoT) is technically a developing model looking at the connectivity of different devices or “things” to each other, as well as with the users and also with the Internet. IoT is projected to be an important necessity for the advancement of intelligent smart homes to facilitate home owners because it provides opportuneness and effectiveness in order to help them attain an improved quality of life. The incorporation of IoT into smart homes entails integrating devices with the Internet. Even though it offers many advantages to the users, it also poses new security and privacy challenges based on connectivity, confidentiality, integrity, authenticity, resource limitation, and adoption immaturity. These challenges make the IoT-based smart homes with limited resources enormously susceptible to diverse forms of security vulnerabilities. Thus, it is pivotal to detect the probable security threats to establish a comprehensive and secure status of smart IOT-based homes. This paper incorporates the security risk assessment approach in order to evaluate the potential security and privacy risks and challenges faced by smart homes. The basic goal of this study is to identify and point up diverse security and privacy threats to smart homes and to unveil the risks for their residents. The paper also presents methods to mitigate the recognized dangers. This study provides a foundation to future applications aimed at refining the security necessities of the IoT-based smart homes.